Case Report: Early Association of Vemurafenib to Standard Chemotherapy in Multisystem Langerhans Cell Histiocytosis in a Newborn: Taking a Chance for a Better Outcome? - Gaspari, Stefania; Di Ruscio, Valentina; Stocchi, Francesca; Carta, Roberto; Becilli, Marco; De Ioris, Maria Antonietta (Frontiers in Oncology, 2021)
Langerhans cell histiocytosis (LCH) is due to aberrant monoclonal proliferation and accumulation of dendritic cells, ranging from a self-limiting local condition to a rapidly progressive multisystem disease with poor prognosis. Pathogenic cells originate from a myeloid-derived precursor characterized by an activation of the MAPK/ERK signaling pathway in about 70% of cases. In particular, BRAF V600E mutation is usually associated with a more severe clinical course and poor response to chemotherapy. We report on a newborn with multisystem LCH in life-threatening medical conditions. At diagnosis, the patient was successfully treated with the early association of BRAF inhibitor Vemurafenib to standard chemotherapy representing a new approach in first-line treatment. A rapid clinical improvement with a prompt fever regression from day 2 and complete resolution of skin lesions by week 2 were observed; laboratory data normalized as well. Vemurafenib was discontinued after 12 months of treatment. No signs of relapse occurred after 12 months of discontinuation. This case indicates that early combination of target therapy with standard treatment may induce rapid response and prolonged disease remission without significant toxicities in infants. This approach represents a valid and safe option as first-line treatment in multisystem disease, especially in high-risk patients.